An evaluation of the impact of tobacco farming on livelihoods and land degradation: a case study of Mount Bokoto ward 24 Murehwa district from 2000-2013 - Mhike, Munyaradzi (Midlands State University, 2015)
This paper presents a review on the literature of tobacco farming on the observed research on the impact of tobacco farming on the livelihoods of smallholder farmers as well its impact on land. In this study I drew on the existing academic structure on tobacco farming in Zimbabwe. An examination of the determinants of farmer partaking in tobacco farming was carried out on 30 smallholder farmers. The case was Mount Bokoto ward24 in Murewa District. This study was therefore initiated with the aims to (i) to evaluate the extent to which tobacco farming has contributed to the degradation of land (ii) to assess how tobacco farming has affected livelihood (iii) to find ways of preventing massive degradation of land due to tobacco farming. Purposive sampling was used to select the smallholder farmers. Questionnaires and interviews were used to collect data. The findings show that tobacco farming improved the livelihoods of smallholder through impacting better income, improved household food security, increased assert ownership, better standard of living, improved household asserts, creation of employment and improved housing structure but however though tobacco farming has improved livelihood it has caused land degradation such as soil erosion, siltation of dams, infiltration, deforestation, desertification, global warming.